“As we are mocked with art” (5.3.68): The Winter’s Tale comme anatomie de la réception - Pierre Iselin (Sillages Critiques)
As in other Shakespearean late plays, The Winter’s Tale, the question of art and the theatre is central, here especially in terms of reception and interpretation, then of hermeneutics. Through direct staging or indirect report, Shakespeare creates theatrical epiphany, but also offers quasi-phenomenological commentaries on wonder. This paper investigates the reception and the dramatic treatment of the Ovidian myth of Pygmalion in the context of the post-Reformation debate over idolatry, and aims to relate the use of complex language and the specific treatment of artefacts or works of art in the play.